Indirect Relationship between Alcoholics Anonymous Spirituality and Their Hopelessness: The Role of Meaning in Life, Hope, and Abstinence Duration - Marcin Wnuk (MDPI AG, 2021)
Spiritual growth is a significant factor in Alcoholics Anonymous treatment process. In the literature, there is an observable lack of research regarding spiritual mechanisms of recovery in alcohol addicted individuals who are participants of self-help groups. The study purpose was to examine the potential mechanisms indirectly influencing participants of Alcoholics Anonymous (AA) and to determine the effects of spiritual experiences on their feelings of hopelessness through finding meaning in life, improving hope, and longer abstinence duration. The study was conducted using a cross-sectional design. Participants were AA meeting attenders from Poland. According to the obtained results, the relationship between spiritual experiences and feelings of hopelessness was indirect through meaning in life, hope, and abstinence duration. Additionally, the moderated mediation effect was positively verified. Meaning in life moderated the relationship between hope and feelings of hopelessness. In a group of AA participants with less-than-average and average levels of meaning in life, hope protected against feelings of hopelessness. Among AA participants with higher-than-average meaning in life, hope was not related to their depression symptoms. The spiritual mechanisms, which led to reduced feelings of hopelessness among AA participants, and the role of meaning in life, hope, and duration of abstinence were confirmed.